Optimasi Antrean Layanan Pengumpulan Formulir Samsat Tandes Surabaya Barat Berbasis Simulasi - Emanuel Necko; Bagas Arjuna (Pusat riset dan Inovasi Nasional, 2025)
The vehicle ownership transfer form submission service at the Samsat Tandes Office in West Surabaya is a vital public service that frequently encounters issues such as long queues and extended waiting times. These conditions lead to user dissatisfaction and reduce the operational efficiency of the institution. This study aims to optimize the existing queuing system through a simulation-based approach to enhance service effectiveness and efficiency. The methodology includes mapping the current service process, collecting data on service times and customer arrivals, and modeling the queuing system using simulation software. Subsequently, several improvement scenarios were analyzed, including the addition of server resources. The simulation results indicate that the scenario involving the addition of one extra server during peak hours yields the most significant impact—reducing average customer waiting time by up to 20% and increasing the number of customers served per day. These findings demonstrate that simple interventions based on simulation analysis can produce substantial improvements in public service quality. In conclusion, a simulation-based approach proves to be effective in supporting strategic decision-making for queue system optimization and is highly recommended for implementation in other public service units facing similar challenges.